Single-Phase Grid Connected Induction Generator with Soft Starting and Power Quality Improvement - Nuttapong Prapurt; Vijit Kinnares (2022 25th International Conference on Electrical Machines and Systems (ICEMS), 2022)
This paper proposes a soft starting method and power quality improvement of a single-phase grid connected induction generator using a phase control thyristor converter and a active filter. The SCR soft starter is used to reduce inrush current and severe electromagnetic oscillation of the generator during startup. The shunt active filter with simple control scheme is introduced for the solution not only harmonic problem associated with the soft starter and nonlinear loads in conjunction with the system but also reactive power drawn by the generator. As a consequence the grid current waveform is close to sinusoidal and the grid power factor is near unity. Investigation and discussion of the system performance by simulation results are given.
Keywords: Wind Turbine Control Systems; Microgrid Control and Optimization; HVDC Systems and Fault Protection